Cattle Water Troughs as Reservoirs of Escherichia coli O157 - LeJeune, Jeffrey T. (American Society for Microbiology, 2001)
Environmental survival of Escherichia coli O157 may play an important role in the persistence and dissemination of this organism on farms. The survival of culturable and infectious E. coli O157 was studied using microcosms simulating cattle water troughs. Culturable E. coli O157 survived for at least 245 days in the microcosm sediments. Furthermore, E. coli O157 strains surviving more than 6 months in contaminated microcosms were infectious to a group of 10-week-old calves. Fecal excretion of E. coli O157 by these calves persisted for 87 days after challenge. Water trough sediments contaminated with feces from cattle excreting E. coli O157 may serve as a long-term reservoir of this organism on farms and a source of infection for cattle.